Anticoagulation after stroke: persistent uncertainties. Issue 1 (22nd February 2022) - Siepen, Bernhard M.; Seiffge, David J.; Fischer, Urs
Abstract : Purpose of review: Direct oral anticoagulants (DOAC) are the mainstay of anticoagulant therapy for stroke prevention in patients with nonvalvular atrial fibrillation. Persistent uncertainties remain in different areas, and this review discusses current dilemmas based on selected studies. Recent findings: Optimal timing of DOAC initiation after a recent ischaemic stroke in patients with atrial fibrillation is currently unknown and subject of ongoing randomized controlled trials. Ischaemic stroke despite anticoagulant therapy in patients with atrial fibrillation is frequent, constitutes heterogeneous causes (competing stroke cause, medication error and cardioembolism despite anticoagulation) and optimal treatment is currently unknown. Thorough etiological work-up is justified. Recent randomized controlled trials found no beneficial effect of DOAC therapy in unselected patients with embolic stroke of undetermined source (ESUS). Currently ongoing trials targeting subgroup of ESUS patients with additional atrial cardiopathy will provide novel data. Cerebral mircobleeds combined in a novel risk score (MICON score) provide good predictive value to stratify the risk of intracranial haemorrhage in patients taking anticoagulants. Use of DOAC after intracerebral haemorrhage in patients with atrial fibrillation is subject of ongoing trials. Summary: There are still significant uncertainties in anticoagulant management in patients with stroke. Ongoing trials will soon provide novel data to improve management of these patients.